2-(Tritylsulfanyl)ethyl 3-iodobenzoate - Zhu, Xin (International Union of Crystallography, 2011)
The triphenylmethyl group in the title compound, C28H23IO2S, has the methine carbon slightly flattened out [ΣCphenyl—C—Cphenyl = 332.8 (6) °]. The –C–O–C–C–S– chain connecting the triphenylmethyl group and the aromatic ring adopts an extended zigzag conformation, these five atoms being approximately co-planar (r.m.s. deviation 0.260 Å).